SCAFFOLDING FOR PEER FEEDBACK SESSION: WHAT, WHY, AND HOW? - Anita Kurniawati (Universitas Katolik Indonesia Atma Jaya, 2013)
Recent research has shown the value of peer feedback in writingclass. By evaluating their peer’s work, students can figure out thestrengths and weaknesses of their friends’ drafts. After doing this, it isexpected that they could compare their peer’s work to their own work,which will certainly be beneficial for the revision process. Thebiggest challenge I faced when implementing peer feedback is how toscaffold the students to be able to provide valuable input to theirfriends’ work. This ability is important because the input studentsgive to their friends could become a reflection to their own draft. Thissharing is based on what I experienced during Expository andArgumentative Writing Class last semester, particularly on what I didbefore, during, and after the peer feedback session. To get clearer ideaabout the classroom situation, I will provide some examples of thetask sheets used. I will also provide some empirical evidence from thestudent worksheets. I expect that my sharing could enrich ourunderstanding on how to use peer feedback sessions, particularly onhow to scaffold the students to provide valuable peer feedback.Keywords: scaffolding, peer feedback